Do Customers Tell Us the Truth? The Bias in Measurement Caused by Anchoring Heuristics - Bialowas, Sylwester (European Scientific Journal, ESJ, 2017)
This article introduces a behavioural economics approach towards decision-making and uses empirical data to indicate how anchoring heuristics might bias measurement results in marketing research. The purpose of the designed research is to decide whether the first piece of information presented to a respondent during an interview might have an influence on their answers. The conclusion that can be drawn from the analysis is that the bias of anchoring heuristics on the households’ saving patterns is very significant. The primary structure of the question order has a considerable effect on further decisions. The analysed case shows that behavioural economics can contribute a lot to understanding customer behaviour and could indeed drive more accurate measurement.